2017
DOI: 10.7326/m17-1531
|View full text |Cite
|
Sign up to set email alerts
|

Does Cognitive Training Prevent Cognitive Decline?

Abstract: Agency for Healthcare Research and Quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
109
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 182 publications
(139 citation statements)
references
References 18 publications
1
109
0
9
Order By: Relevance
“…The potential of digital activities for brain training either to reduce dementia risk has attracted much popular attention. However, while there is consistent evidence of improvement in the aspect of cognitive function that is trained (e.g., processing speed), to date there is no substantial evidence for dementia prevention or delaying decline [63]. However, the FINGER trial has demonstrated that computerised cognitive training can be beneficial in reducing dementia risk as one part of a multidimensional lifestyle intervention [64].…”
Section: Introductionmentioning
confidence: 99%
“…The potential of digital activities for brain training either to reduce dementia risk has attracted much popular attention. However, while there is consistent evidence of improvement in the aspect of cognitive function that is trained (e.g., processing speed), to date there is no substantial evidence for dementia prevention or delaying decline [63]. However, the FINGER trial has demonstrated that computerised cognitive training can be beneficial in reducing dementia risk as one part of a multidimensional lifestyle intervention [64].…”
Section: Introductionmentioning
confidence: 99%
“…Ta èiau në ra iki ga lo áro dy ta, ar kog ni ty vi nës tre ni ruo tës tik rai duo da tei gia mà efek tà kogni ty vi niams þmo niø ge bë ji mams ir ar ga li bû ti nau do ja mos ADRD ir MCI pre ven ci jai. Ið 35 iden ti fi kuo tø kli ni ki niø ban dy mø, re mian tis ða lið ku mo kri te ri ju mi, at rink ta 11 tyri mø, ið ku riø 6-iuo se da ly va vo nor ma liø kog ni ty vi niø gebë ji mø as me nys, o li ku siuo se 5 ty ri muo se -da ly viai, tu rintys leng và kog ni ty vi ná su tri ki mà [72].…”
Section: Kognityvinës Treniruotësunclassified
“…Dau gu ma þmo niø, da ly vau jan èiø kog ni ty vi në se tre niruo të se, ti ki si ið veng ti de men ci jos ar su si ju siø kog ni ty viniø su tri ki mø, ta èiau, rem da mie si nag ri në tais ty ri mais, nega li me da ry ti ið va dø, kad kog ni ty vi nës tre ni ruo tës tu ri áta -kos ti ki my bei su sirg ti ADRD ar MCI [72]. Dau gu ma ty rimø ne mi në jo re zul ta tø, su si ju siø su ADRD ar MCI, o pagrin di niai sëk min gø kog ni ty vi niø tre ni ruo èiø ro dik liai buvo kog ni ty vi niø tes tø re zul ta tai.…”
Section: Kognityvinës Treniruotësunclassified
See 1 more Smart Citation
“…According to recent systematic reviews, there is insufficient evidence for the cognitive benefits of single‐component physical activity . Alternatively, cognitive training can improve intellectual function, but these gains are generally restricted to the training domain . The Finnish Geriatric Intervention Study to Prevent Cognitive Impairment and Disability (FINGER) study reported that multidomain intervention including diet, exercise, cognitive training, and vascular risk monitoring improved multidomain neuropsychological test performance .…”
Section: Introductionmentioning
confidence: 99%